Post 9-11 U.S. muslim labor market outcomes - Faisal Rabby; William M. Rodgers (Institute for the Study of Labor (IZA), 2009)
Using a difference-in-differences framework and micro data from the Current Population Survey-Merged Outgoing Rotation Group Files (1999 to 2004), this paper estimates the impact that the 9-11 terrorists attacks had on the U.S. labor market outcomes of individuals with nativity profiles similar to the terrorists. We find that shortly after the attacks, the employment-population ratios and hours worked of very young (ages 16 to 25) Muslim men fell. By 2004, most losses had begun to dissipate. The employment-population ratios and hours worked of older Muslim men experienced little deterioration.
Keywords: J15; J61; J71; 330; Muslim; 9/11; labor market outcomes; immigrant workers; Migranten; Islam; Araber; Arbeitsmarktdiskriminierung; Arbeitszeit; USA